Cytotoxicity study of some Ti alloys used as biomaterial - Donato, Tatiani A. G. [UNESP]; de Almeida, Luciano H. [UNESP]; Nogueira, Renata A. [UNESP]; Niemeyer, Terlize C. [UNESP]; Grandini, Carlos Roberto [UNESP]; Caram, Rubens; Schneider, Sandra G.; Santos, Arnaldo R. (Elsevier B.V., 2009)
An implanted material is considered biocompatible, if adverse and uncontrollable reactions don't exist in the biological system. in this sense, biocompatibility tests made in the constituent materials are very important so that the implants have Success. The in vitro cytotoxicity tests represent the initial phase of the process, and Could be considered as a pre-selection of those materials. in vitro techniques using cell culture have become widely used in the evaluation of biomaterial cytotoxicity, which has contributed to their standardization and the substitution of in vivo tests. This paper shows a study of the in vitro cytotoxicity of two Ti based alloys, Ti-13Nb-13Zr and Ti-35Nb-7Zr-5Ta, in the as-received condition and after heat treated. The results show that the alloys presented no cytotoxic effects in the studied conditions. (C) 2008 Elsevier B.V. All rights reserved.
Keywords: Biocompatibility; Ti alloys; Cytotoxicity; Cell culture